What do we know about the future of agrifood systems in Southeast Asia? - Tran, Nhuong; Valera, Harold Glenn; Chan, Chin Yee; Pede, Valerien Olivier; Aung, Yee Mon; Antonio, Ronald Jeremy (International Food Policy Research Institute, 2025)
The food systems of Southeast Asia (SEA) are projected to be under increasing pressure due to multiple drivers, including population growth, urbanization, biodiversity loss, and the uncertainties stemming from climate change.